2021
DOI: 10.3390/su13041742
|View full text |Cite
|
Sign up to set email alerts
|

Planning Walkable Neighborhoods for “Aging in Place”: Lessons from Five Aging-Friendly Districts in Singapore

Abstract: Today, “walkability” is considered a critical component of an aging-friendly neighborhood. This study examined the relationships between the neighborhood physical environment, walkability, and physical activity levels of older residents in Singapore. Five neighborhoods notable for their “aging in place” strategies were selected for a site survey. A questionnaire focusing on the evaluation of neighborhood walkability was administered to older adults in these neighborhoods. The questionnaire included three secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…The findings suggest that some of these factors are associated with both age and self-reported health condition. Such results correspond to some recent local studies which observed the connection between environmental conditions, going out and outdoor behaviour, and physical, psychological and social well-being of elderly residents (e.g., [ 115 , 116 , 117 , 118 , 119 ]). For instance, in their qualitative study, Bhuyan and Yuen [ 120 ] concluded that older adults tend to associate safety and pedestrian-friendly features with physical health, public amenities with social well-being, and aesthetic appeal and wayfinding with mental health.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings suggest that some of these factors are associated with both age and self-reported health condition. Such results correspond to some recent local studies which observed the connection between environmental conditions, going out and outdoor behaviour, and physical, psychological and social well-being of elderly residents (e.g., [ 115 , 116 , 117 , 118 , 119 ]). For instance, in their qualitative study, Bhuyan and Yuen [ 120 ] concluded that older adults tend to associate safety and pedestrian-friendly features with physical health, public amenities with social well-being, and aesthetic appeal and wayfinding with mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Research by Hou and colleagues [ 116 ], for instance, indicated a significant positive association between the proximity to wet markets and an increased tendency in residents to walk more frequently. On the other hand, a study by Tao and colleagues [ 118 ] suggested that a greater number of nearby amenities significantly decreases the average walking time and daily activity levels of older adults, which calls for more careful planning of neighbourhood facilities to promote physical activity among the elderly residents.…”
Section: Discussionmentioning
confidence: 99%
“…Gender, marital status, education level, income, social activity level [25,48] Religion, number of family members [26] House/Housing Convenience of housing structure: interior space inside a house [28][29][30][31][32][33][34][35][36][37] Home ownership status [26,28] Period of residence in the current home [26] Housing type [25] Housing satisfaction [25] Ecologically friendly features: ventilation and air quality [8] Community Convenient living conditions and accessibility of the neighborhood facilities [6,17,32,36] Pedestrian environment, convenience and safety of transportation and utilization facilities [6,12,28,29,[38][39][40][41] Regional senior citizens' facilities [38] Location of a house [28,[34][35][36]38] Safe neighbors [6] Well-organized and environmentally friendly buildings [12,14,[41][42][43][44][45] Se...…”
Section: Personalmentioning
confidence: 99%
“…Community factors affecting AIP include convenient living conditions, neighborhood conditions [6,17,24], pedestrian environments, convenience and safety of transportation and amenities [6,12,28,29,[38][39][40], and safe neighbors [6]. As the elderly become older, they want to keep major amenities such as shops, maintenance facilities, and public transportation within walking distance or close distance of their homes [36].…”
Section: Personalmentioning
confidence: 99%
See 1 more Smart Citation